PARTNERSHIP AND DIVERSIFICATION AS FACTORS IN THE FORMATION OF A SERVICE-ORIENTED BUSINESS MODEL OF HOTEL AND RESTAURANT BUSINESS ENTERPRISES - SAHAIDAK, Mykhailo (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of directions and approaches to the formation and implementation of a service-oriented business model of hotel and restaurant business enterprises on the basis of strategic partnership and diversification. The article defines and characterizes the main features and structures the key elements that, in interaction, allow creating an effective service-oriented business model, the implementation of which will contribute to the success of the service sector enterprise in the conditions of the modern business environment. It is proposed to develop a service-oriented business model using the toolkit of holistic marketing, as an extended, integrated approach, which consists in understanding the importance of establishing and maintaining long-term relationships of hotel and restaurant business enterprises with customers and business partners. The article defines, characterizes and substantiates the diversification of partnerships as a strategic approach that contributes to ensuring stability and efficiency in the interaction of the enterprise with various organizations of various spheres and directions of activity and provides for the expansion and diversity of interaction. The key indicators for measuring the effectiveness of the service-oriented business model were determined and it was proved that the diversification strategy allows to reduce the risk associated with the dependence of hotel and restaurant business enterprises on a specific market segment, to attract various heterogeneous groups of customers, to quickly adapt to changes in economic or socio-cultural condition and stimulate innovation in improving the quality of service. The theoretical results of the article were obtained using a systematic approach to the study of definitions of partnership and diversification, as factors in the formation of a service-oriented business model in their interconnection and interdependence. Scientific abstraction, theoretical generalization and comparison, analysis and synthesis, system analysis, graphical presentation of the obtained results were also used as research methods.
Keywords: partnership; strategic partnership; diversification strategy; diversification of partnerships; service-oriented business model; holistic marketing; efficiency; hotel and restaurant business; service provider company